ModelsystemforgrowingandquantifyingStreptococcuspneumoniaebiofilms insitu andin realtime (International Journal of Food and Nutritional Sciences, 2022)
By ATR/FTIR, which stands for attenuated total reflection and Fourier transform infrared spectroscopy, it was possible to see how the harmful bacterium Streptococcus pneumoniae forms biofilms on surfaces and multiplies. One of the most typical causes of ear infections in infants and one of the species suspected to create biofilms in those with otitis media, this particular organism was chosen due to its clinical importance (5).ATR/FTIR and Epifluorescence microscopy are two techniques that, When combined, they allow for the simultaneous observation of the S. pneumoniae biofilm's IR spectrum as it forms and offer a way to measure total and viable cell counts at various growth stages. In contrast to earlier ATR/FTIR investigations, this technique investigates how biofilms develop on surfaces